Bright lenses are easy to find: spectroscopic confirmation of lensed quasars in the Southern Sky. Issue 3 (17th December 2018) - Spiniello, C; Agnello, A; Sergeyev, A V; Anguita, T; Rodríguez, Ó; Napolitano, N R; Tortora, C
ABSTRACT: Gravitationally lensed quasars are valuable, but extremely rare, probes of observational cosmology and extragalactic astrophysics. Progress in these fields has been limited just by the paucity of systems with good ancillary data. Here we present a first spectroscopic confirmation of lenses discovered in the Southern Sky from the DES and KiDS-DR3 footprints. We have targeted seven high-graded candidates, selected with new techniques, with NTT-EFOSC2, and confirmed five of them. We provide source spectroscopic redshifts, image separations, gri photometry, and first lens model parameters. The success rate of ${\sim } 70{{\ \rm per\ cent}}$ confirms our forecasts, based on the comparison between the number of candidate doubles and quadruplets in our searches over a ≈5000 deg 2 footprint and theoretical predictions.